2011
DOI: 10.1002/bbb.306
|View full text |Cite
|
Sign up to set email alerts
|

Policies and instruments affecting water use for bioenergy production

Abstract: Conference PaperIFPRI5EPTDNon-P

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 49 publications
0
12
0
3
Order By: Relevance
“…The most water-intensive aspect of biofuel production is growing the feedstock (Moraes et al, 2011). The amount of water used may appear minor at the global level but water requirements for biofuel production must be viewed in the context of local water resources, especially when irrigation water is required.…”
Section: Primary Energy Extractionmentioning
confidence: 99%
“…The most water-intensive aspect of biofuel production is growing the feedstock (Moraes et al, 2011). The amount of water used may appear minor at the global level but water requirements for biofuel production must be viewed in the context of local water resources, especially when irrigation water is required.…”
Section: Primary Energy Extractionmentioning
confidence: 99%
“…Governments could furthermore create direct incentives for rainfed bioenergy production through taxes and subsidies. South Africa has for example already decided to stop the support for bioenergy crops under irrigation (Moraes et al, 2011).…”
Section: Policy Implications and Conclusionmentioning
confidence: 99%
“…Ramos (2011) worked on four probable future scenarios, simulating water demand from the Poechos system for different crops, and showed that expanding the cultivation of sugarcane would affect water availability in the Chira-Piura regulated water system, leading to a decline in water availability. Other studies similarly demonstrated biofuels impacts on water and the environment (Delucchi 2010;Elcock 2010;Gerbens-Leenes et al 2009;Huffaker 2010;Moraes et al 2011;Perrone and Hornberger 2014). Nonetheless, the central government systematically overlooked these studies in favor of bioethanol production, thus aggravating the situation of the Chira Basin.…”
Section: Biofuels Investment and Water Demand In Chiramentioning
confidence: 85%